Government Report on Finnish Foreign and Security Policy - Ministry for Foreign Affairs of Finland (Finnish Government, 2020)
The Government Report examines the Finland's foreign and security policy environment, which is in an intense state of flux, and defines the goals and priorities of Finnish foreign and security policy. By implementing it, the Government strengthens Finland's security and prosperity. The goals include promoting foreign and security policy cooperation, strengthening multilateral cooperation, sharing global responsibilities and peacebuilding. These goals are implemented by the following means: enhancing the European Union's coherence and capacity to act, emphasising our special relationship with Sweden and Nordic cooperation, developing NATO partnership, maintaining bilateral relations and partnerships, enhancing our security by means of high crisis resilience, supporting the rules-based international system, striving for a more effective UN system, defending open and fair trade, seizing the opportunities of digitalisation, emphasising the importance of Arctic cooperation, emphasising human rights as foundation of foreign and security policy, producing security by mitigating climate change, taking action to strengthen global health security, promoting sustainable development, responding to migration in a comprehensive manner, strengthening our mediation competence, creating stability by means of crisis management, and generating predictability by means of arms control and disarmament.